Answer:
Prime
Step-by-step explanation:
x² + 20x − 36
You must find a pair of numbers that multiply to give -36 and add to give +20.
The likely candidates are 2 and 18, and they must have opposite signs to give a negative product.
+2 × (-18) = -36; +2 + (-18) = -16
-2 × 18 = -36; -2 + 8 = +16
Neither combination gives +20 as the sum.
The expression can't be factored with rational numbers.
The expression is prime.
Answer:
(4/3, 7/3)
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
<u>Algebra I</u>
- Terms/Coefficients
- Coordinates (x, y)
- Solving systems of equations of using substitution/elimination
Step-by-step explanation:
<u>Step 1: Define Systems</u>
7x - y = 7
x + 2y = 6
<u>Step 2: Rewrite Systems</u>
Equation: x + 2y = 6
- [Subtraction Property of Equality] Subtract 2y on both sides: x = 6 - 2y
<u>Step 3: Redefine Systems</u>
7x - y = 7
x = 6 - 2y
<u>Step 4: Solve for </u><em><u>y</u></em>
<em>Substitution</em>
- Substitute in <em>x</em>: 7(6 - 2y) - y = 7
- Distribute 7: 42 - 14y - y = 7
- Combine like terms: 42 - 15y = 7
- [Subtraction Property of Equality] Subtract 42 on both sides: -15y = -35
- [Division Property of Equality] Divide -15 on both sides: y = 7/3
<u>Step 5: Solve for </u><em><u>x</u></em>
- Define original equation: x + 2y = 6
- Substitute in <em>y</em>: x + 2(7/3) = 6
- Multiply: x + 14/3 = 6
- [Subtraction Property of Equality] Subtract 14/3 on both sides: x = 4/3
1/3 of the dimensions means to divide the dimensions by 3. This is to figure out what 1/3 of the dimensions are.
Our length is 6, and our width is 9.
Let's divide our length first.
6/3 = 2.
Our length with 1/3 of it's original dimensions is 2.
Let's divide our width now.
9/3 = 3.
Our width with 1/3 of it's original dimensions is 3.
Our dimensions are 2 by 3.
Your answer is A.) 2 in. by 3 in.
I hope this helps!
Answer:
<em>Hence the daughter's present age is 15 years</em>
<em>The fathers present age is 35 years</em>
<em></em>
Step-by-step explanation:
Let the present age of daughter be x
Let the present age of father be y
5 years ago;
Daughter's age = x - 5
Fathers age = y - 5
If the present age of father is thrice as old as the age of daughter 5 years ago, then;
y - 5 = 3(x-5)
y - 5 = 3x-15
y = 3x - 10 .... 1
In 5 years time;
Daughters age = x + 5
Fathers age = y + 5
If the age of father will be twice the age of his daughter in 5 years time then;
y+5 = 2(x+5)
y+5 = 2x + 10
y = 2x + 5 .....2
Equate 1 and 2;
3x - 10 = 2x + 5
3x - 2x = 5 + 10
x = 15
Since y = 2x + 5
y = 2(15) + 5
y = 35
<em>Hence the daughter's present age is 15 years</em>
<em>The fathers present age is 35 years</em>
<em></em>